HUBUNGAN FAKTOR EKOLOGI DAN POLA ASUH DENGAN STATUS GIZI PADA BALITA DI DESA DAMARGUNA KECAMATAN CILEDUG KABUPATEN CIREBON TAHUN 2020 - Farah Abubakar (2021)
During the toddler years there is a process of rapid growth and development, while that age is also quite susceptible to various diseases and malnutrition (excess and malnutrition). Things are influenced by the environment such as sanitation and family care. This study aims to determine the relationship between ecological factors and parenting style with the nutritional status of children under five in Damarguna Village, Ciledug District, Cirebon Regency. The quantitative research method used a cross sectional design. The sample consisted of 211 toddlers with purposive sampling technique. The research site was in Damarguna Village, Ciledug District, Cirebon Regency which was held in October 2020 - January 2021. The data collection instruments used a scale, microtoise, and KMS (Growth Chart). This study used univariate analysis and bivariate analysis with the Chi-Square test. The results showed the factors related to the nutritional status of children under five, namely environmental sanitation (p-value = 0,000) and nutritional parenting (p-value = 0,000). There is a significant relationship between environmental sanitation and nutritional parenting with the nutritional status of children under five. Mothers or caregivers for toddlers are advised to always monitor the growth and development of their children by taking them to the posyandu regularly, paying attention to the nutritional intake provided, and maintaining personal and environmental hygiene.